Randomized Phase 2 Study of ACE-083 in Patients With Charcot-Marie-Tooth Disease. (7th June 2022) - Thomas, Florian P.; Brannagan, Thomas H.; Butterfield, Russell J.; Desai, Urvi; Habib, Ali A.; Herrmann, David N.; Eichinger, Katy J.; Johnson, Nicholas E.; Karam, Chafic; Pestronk, Alan; Quinn, Colin; Shy, Michael E.; et al.
Abstract : Background and Objectives: The goal of this work was to determine whether locally acting ACE-083 is safe and well tolerated and increases muscle volume, motor function, and quality of life (QoL) in adults with Charcot-Marie-Tooth disease (CMT) type 1. Methods: This phase 2 study enrolled adults with CMT1 or CMTX (N = 63). Part 1 was open label and evaluated the safety and tolerability of different dose levels of ACE-083 for use in part 2. Part 2 was a randomized, placebo-controlled, 6-month study of 240 mg/muscle ACE-083 injected bilaterally into the tibialis anterior muscle, followed by a 6-month, open-label extension in which all patients received ACE-083. Pharmacodynamic endpoints included total muscle volume (TMV; primary endpoint), contractile muscle volume (CMV), and fat fraction. Additional secondary endpoints included 6-minute walk test, 10-m walk/run, muscle strength, and QoL. Safety was assessed with treatment-emergent adverse events (TEAEs) and clinical laboratory tests. Results: In part 1 (n = 18), ACE-083 was generally safe and well tolerated at all dose levels, with no serious adverse events, TEAEs of grade 3 or greater, or death reported. In part 2 (n = 45 enrolled, n = 44 treated), there was significantly greater change in TMV with ACE-083 compared with placebo (least-squares mean difference 13.5%; p = 0.0096). There was significant difference between ACE-083 and placebo for CMV and change in ankle dorsiflexion strength. Fat fraction and all other functional outcomes were not significantly improved by ACE-083. Moderate to mild injection-site reactions were the most common TEAEs. Discussion: Despite significantly increased TMV and CMV, patients with CMT receiving ACE-083 in tibialis anterior muscles did not demonstrate greater functional improvement compared with those receiving placebo. Trial Registration Information: Clinical Trials Registration: NCT03124459. Classification of Evidence: This study provides Class II evidence that intramuscular ACE-083 is safe and well tolerated and increases total muscle volume after 6 months of treatment in adults with CMT1 or CMTX.